Translating school health research to policy. School outcomes related to the health environment and changes in mathematics achievement. (1st October 2015) - Snelling, Anastasia M.; Belson, Sarah Irvine; Watts, Erin; George, Stephanie; Van Dyke, Hugo; Malloy, Elizabeth; Kalicki, Michelle
Highlights: Exploring school health policy on student performance and health status. We examine school-level data to explore the relationship between health and learning. Further work is necessary to describe the relationship between obesity and student learning. Abstract: This paper describes an exploration of the relationship between mathematic achievement and the school health environment relative to policy-driven changes in the school setting, specifically with regard to physical education/physical activity. Using school-level data, the authors seek to understand the relationship between mathematics achievement and the school health environment and physical education minutes. This work provides a description of the aspects of the school health environment, an exploration of the interrelationships between school health and student achievement, and an assessment of the effects of the school health policy and practice on student performance and health status. Based on these findings, we identify additional research necessary to describe the relationship between obesity and learning in children.